2019
DOI: 10.1088/1757-899x/640/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of abattoir activities on the physicochemical properties of soils within a residential area of Omu-Aran, Nigeria.

Abstract: Waste effluents from abattoirs have been documented to have harmful effects on the soil media. There is little information about the level of contamination by abattoir effluents on the soil media in Omu-Aran. This study therefore assessed soil samples for possible contamination of physicochemical parameters and heavy metals from different points and some meters away from the mini abattoir in Omu-Aran, Kwara State, Nigeria. Soil samples which are 18 in number were collected from the soil around wells which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…The samples had mean electrical conductivity values in the following decreasing order: D1> D2> D3> D4> control. The mean electrical conductivity values of the sampling points D1 -4 and control met the WHO recommended permissible limits.Elemile et al,23 reported higher mean electrical conductivity values of 79.60±4.2 and 55.43±4.94 µS/cm for soils around the abattoir in Omu -Aran, Kwara State than what was obtained for EC in the studied soil samples. Accordingly, they stated that the increase in electrical conductivity in the soils around abattoirs could be due to the build-up of wastes such as bones, hairs, flesh and blood in abattoir effluents.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…The samples had mean electrical conductivity values in the following decreasing order: D1> D2> D3> D4> control. The mean electrical conductivity values of the sampling points D1 -4 and control met the WHO recommended permissible limits.Elemile et al,23 reported higher mean electrical conductivity values of 79.60±4.2 and 55.43±4.94 µS/cm for soils around the abattoir in Omu -Aran, Kwara State than what was obtained for EC in the studied soil samples. Accordingly, they stated that the increase in electrical conductivity in the soils around abattoirs could be due to the build-up of wastes such as bones, hairs, flesh and blood in abattoir effluents.…”
mentioning
confidence: 52%
“…Organic carbon content in the soil plays a vital role in the soil development, fertility and moisture availability. 23 stated that if the concentration of phosphorus in the soil exceeds the acceptable limits, it could lead to the under development of plants growth and equally restricts the uptake of nitrogen by plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these sources are not regulated as they are done by private individuals while appropriate steps ensuring safe and sustainable water supply are often ignored. These water sources become easily polluted from waste arising from human activities, infiltrating sewage effluent and wash-down of contaminated soil surfaces [9,10]. The soil media can also play a major role in polluting groundwater.…”
mentioning
confidence: 99%
“…The soil media can also play a major role in polluting groundwater. This is because soils can be laden with toxic metals and harmful organic substances which eventually find their way into water streams via infiltration [10]. In studies regarding water quality, surface waters and boreholes (deep wells) have received majority of the attention [11] whereas there is limited information on the status of shallow wells, but shallow wells are among the most important water sources in many sub-Saharan African rural areas [12,13].…”
mentioning
confidence: 99%